Bacillus and Streptomyces were selected as broad‐spectrum antagonists against soilborne pathogens from arid areas in Egypt. Issue 2 (11th February 2013) - Köberl, Martina; Ramadan, Elshahat M.; Adam, Mohamed; Cardinale, Massimiliano; Hallmann, Johannes; Heuer, Holger; Smalla, Kornelia; Berg, Gabriele
Abstract Plant protection via disease‐suppressive bacteria in desert farming requires specific biological control agents (BCAs) adapted to the unique arid conditions. We performed an ecological study of below‐ground communities in desert farm soil and untreated desert soil, and based on these findings, selected antagonists were hierarchically evaluated. In contrast to the highly specific 16S rRNA fingerprints of bacterial communities in soil and cultivated medicinal plants, internal transcribed spacer profiles of fungal communities were less discriminative and mainly characterised by potential pathogens. Therefore, we focused on in vitro bacterial antagonists against pathogenic fungi. Based on the antifungal potential and genomic diversity, 45 unique strains were selected and characterised in detail. Bacillus/Paenibacillus were most frequently identified from agricultural soil, but antagonists from the surrounding desert soil mainly belonged to Streptomyces. All strains produced antibiotics against the nematode Meloidogyne incognita, and one‐third showed additional activity against the bacterial pathogen Ralstonia solanacearum. Altogether, 13 broad‐spectrum antagonists with antibacterial, antifungal and nematicidal activity were found. They belong to seven different bacterial species of the genera Bacillus and Streptomyces. These Gram‐positive, spore‐forming bacteria are promising drought‐resistant BCAs and a potential source for antibiotics. Their rhizosphere competence was shown by fluorescence in situ hybridisation combined with laser scanning microscopy.